KEANEKARAGAMAN JENIS LAMUN SEBAGAI SUMBER PAKAN DUGONG DUGON PADA DESA BUSUNG BINTAN UTARA KEPULAUAN RIAU - Juraij Juraij; Dietriech G Bengen; Mujizat Kawaroe (Journal Omni-Akuatika, 2014)
Seagrass species diversity as a source of feed Dugong dugon was studied in Busung North Bintan, Riau Islands during November 2014. The purpose of this study is to determine the diversity of seagrass species found on the feeding ground area. Data collection on seagrass diversity was conducted with three transect lines follow the shoreline, the distance between the transect line is 25 meters. Each transect lines was observed with the aid seagrass quadrant transects (50 x 50 cm plot) starting from the point 0 m and repeated every 10 m distance. The results showed that the diversity of seagrass type found in the waters of Busung North Bintan consist of Cymodoceae serrulata, Halophila minor, Syringodium isoetifolium, H. spinosa and Halodule uninervis, five types are a food source for the Dugong dugon. Amongst them, H. uninervis has highest value in term of their abundance and coverage.Keywords : Type of seagrass, dugongs feed, Halodule uninervis, Dugong dugon